Effect of age at first calving on reproductive parameters in the first lactation of Holstein and Jersey cattle from Costa Rica - Castillo Badilla, Gloriana (2016)
A retrospective study including 28,367 purebred Jersey and 46,029 purebred Holstein cattle, from specialized dairy farms of different ecological areas in Costa Rica was conducted from 2000 to 2010 in order to quantify the effect of age at first calving (AFC) on the reproductive parameters of the first lactation. Data included records in the VAMPP Bovino 3.0 software from the Regional Information Technology Center for Sustainable Animal Production (CRIPAS) of the School of Veterinary Medicine, National University of Costa Rica. Data was analyzed using descriptive statistics and a linear mixed model. The results showed a significant effect of age at first calving (AFC) in the calving to conception interval (CCI) of Holstein cows (P<0.001), with -13 and -6 days for cows with AFC <26 months and AFC 26-33months, respectively. CCI was not significantly affected in Jersey cows (P=0.25). In addition, average services per conception (SPC) corresponded to 1.44 (D.E. 0.83/IC95%: 1.44 – 1.44) for Holstein cows and 1.48 (D.E. 0.93/ IC95%: 1.46 – 1.49) for Jersey animals. This parameter was significantly influenced by AFC in both breeds (P<0.0001), with a decreased SPC in 1.1 in Holstein and 0.6 in Jersey cows, in those animals with low and medium AFC, compared to high AFC. Consequently, the increment in AFC, adjusted by environmental, management and intrinsic variables of the cow, had a negative effect over the CCI of the first lactation of Holstein cows, but not in Jersey animals; similarly, there was a negative effect of the AFC over SPC in both breeds.